A cost analysis of reductions in work productivity for MG patients and their caregivers by symptom severity - Dewilde, Sarah; Qi, Cynthia Z.; De Ruyck, Femke; Paci, Sandra; Van de Veire, Lucas; Griffiths, Alison; Wolfe, Gil I.; Mantegazza, Renato; Phillips, Glenn (Frontiers in Public Health, 2025)
IntroductionMyasthenia Gravis (MG) is a debilitating autoimmune disorder associated with fatigue and weakness in the ocular, respiratory, bulbar and limb muscles. This study evaluates productivity losses for MG patients and their caregivers by MG symptom severity.MethodsIn the multinational MyRealWorld-MG study, 1,049 MG patients and caregivers reported on work productivity (sick leave, reduced working hours, early retirement). Productivity losses were calculated using the average wage per hour. A UK perspective was adopted for the whole sample, and country-specific analyses were conducted for Italy, Spain and the US. The MG-Activities of Daily Living (MG-ADL) score was used to estimate the association between symptom severity and productivity losses, with patients categorized as having mild (0–4), moderate (5-9), or severe (> = 10) symptoms.ResultsIn the MyRealWorld-MG study, 36.5% of MG patients reported taking sick leave within the last month and 11.4% reported stopping work (or retiring early) due to MG. Furthermore, 36.0% required caregiver support with 14.6% of caregivers reducing working hours and 13.4% stopping work. Mean productivity losses were £16,630/year for patients and caregivers combined, largely attributable to patient productivity losses (£13,891). Patients with severe MG incurred 3.8 times more productivity losses compared to patients with mild disease. Productivity loss estimates varied between Italy, Spain and the US.ConclusionThe impact of MG on patients’ and caregivers’ work productivity leads many of them to reduce work hours or retire early, resulting in significant productivity losses. The magnitude of these productivity losses is correlated with symptom severity and varies by country.